2019
DOI: 10.4209/aaqr.2019.10.0503
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Carbon Dioxide Emissions through Energy-saving Renovation of Existing Buildings

Abstract: The rapid expansion of the worldwide tourism industry has significantly increased energy consumption in hotels. Hence, the renovation of existing hotel buildings is relevant to achieving the energy-saving goals of the construction sector. This study takes a hotel in eastern China as an example of energy-saving renovation. First, based on a BECS energy-saving design and SPSS statistical analysis software, the energy-saving effects of renovation of building envelope (windows, walls, and roofs) are dynamically si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…At present, the amount of CO2 in the atmospheres is nearly 50% higher than in 1750 (Su et al, 2020). CO2 emissions have globally received more and more attention, including greenhouse effects, health of ecosystems, radiative forcing, global carbon cycle, reduction of carbon dioxide emissions, as well as CO2 capture and geological storage (Cai et al, 2019;Xiang et al, 2019;Yang et al, 2019). Atmospheric quality deterioration has occurred in Asian, European and North American cities in recent years, and especially in some rapidly developing regions and countries (Li et al, 2018).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…At present, the amount of CO2 in the atmospheres is nearly 50% higher than in 1750 (Su et al, 2020). CO2 emissions have globally received more and more attention, including greenhouse effects, health of ecosystems, radiative forcing, global carbon cycle, reduction of carbon dioxide emissions, as well as CO2 capture and geological storage (Cai et al, 2019;Xiang et al, 2019;Yang et al, 2019). Atmospheric quality deterioration has occurred in Asian, European and North American cities in recent years, and especially in some rapidly developing regions and countries (Li et al, 2018).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…As a result of these observations, we suggest that carbon dioxide-leakage levels increase owing to fracture opening, potentially caused by changes in fault architecture and permeability structure of regions surrounding the faults. (Yang et al, 2019;Xiang et al, 2019) and the crustal tilt observation in cavern (Yamamoto et al, 2004;Chen et al, 2015) can be found in references. Eventually, we have examined measurements of data from Jan. 1, 2019 to Aug. 31, 2019, during which period both crustal tilt and carbon dioxide levels are simultaneously recorded.…”
Section: Accepted Manuscriptmentioning
confidence: 99%